A current source inverter with series AC capacitors for transformerless grid-tied photovoltaic applications - Photong, Chonlatee (2013)
The Current Source Inverter (CSI) is one of the simplest power converter topologies that can convert DC to AC and feed power generated from photovoltaic (PV) cells into the AC grid with a single power conversion stage over the whole PV voltage range. The CSI also provides smooth DC current which is one of the requirements of the PV cells as well as preventing reverse current using unidirectional switches. However, the CSI operates with low efficiency at lower PV voltages, which is where the PV cells produce maximum output power. This low efficiency is caused by large differences in voltage levels between the PV side and the grid side across the converter.